Relational apologetics : Christian faith with hiliness, respect and truth - Sherrard, Michael C. (S.l. : CreateSpace Independent Publishing Platform, 2012)
How do you know that there is a God? How do you answer someone who says that truth doesn$1 (Bt exist? What do you do when someone asks you how you know that Christianity is the right religion? If you are like many people, the only answer you can offer is, (3z(BWell... I just have faith.(3y (BBut to a world that wants to know if God is real, this is not a good enough answer. Christians must be ready to give a reason, a good reason, for their hope in Jesus, and their lives must be a holy reflection of their message. In Relational Apologetics, Michael C. Sherrard seeks to help Christians do just that: become holy people that defend Christianity both in word and deed. Using stories and drawing upon personal experiences, Sherrard teaches the importance of personal holiness, treating skeptics with respect, engaging in authentic conversations instead of shouting matches, and having well thought out answers to the skeptic's questions. In the process, you$1 (Bll learn that defending Christianity is as much about who you are and what you do as it is what you say. And you will find that your life is intended to be an apologetic for God and a light for men to find Him.s
Keywords: Apologetics